Japoński model zarządzania zasobami ludzkimi - Przytuła, Sylwia (Japanese model of human resources management, 2009)
The purpose of this article is to present the Japanese model of management determined by the cultural factors. Cultural background is very important to explain implications for HRM (for recruitment, motivation, development, and compensation) in Japanese corporations operating in the global market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 382-392